Digital and Analog Resistive Switching Behavior in Si-NCs Embedded in a Si/SiO2 Multilayer Structure for Neuromorphic Systems - Alfredo Morales-Sánchez; Karla Esther González-Flores; Sergio Alfonso Pérez-García; Sergio González-Torres; Blas Garrido-Fernández; Luis Hernández-Martínez; Mario Moreno-Moreno (Nanomaterials, 2023)
In this work, we report the digital and analog resistive-switching (RS) characteristics in a memristor based on silicon nanocrystals (Si-NCs) integrated into a complementary metal-oxide-semiconductor (MOS) structure. Si-NCs with a diameter of 5.48 ± 1.24 nm embedded in a SiO2/Si-NCs/SiO2 multilayer structure acts as an RS layer. These devices exhibit bipolar RS with an intermediate resistance step during SET and RESET processes, which is believed to lie in the Si-NCs layer acting as charge-trapping nodes. The endurance studies of about 70 DC cycles indicate an ON/OFF ratio of ~106 and a retention time larger than 104 s. Long-term potentiation (LTP, −2 V) and long-term depression (LTD, +4 V) are obtained by applying consecutive identical pulse voltages of 150 ms duration. The current value gradually increases/decreases (LTP/LTD) as the pulse number increases. Three consecutive identical pulses of −2 V/150 ms (LTP) separated by 5 and 15 min show that the last current value obtained at the end of each pulse train is kept, confirming an analog RS behavior. These characteristics provide a possible way to mimic biological synapse functions for applications in neuromorphic computing in Si-NCs-based CMOS structures.